Behaviors of CH4 hydrate formation in cold seeps with underlying gas plume. (15th November 2021) - Guo, Xianwei; Shi, Kangji; Guan, Dawei; Lv, Xin; Li, Qingping; Dong, Hongsheng; Zhao, Jiafei; Yang, Lei; Liu, Zheyuan
Graphical abstract: Highlights: Hydrate formation induced by cold seeps is first investigated by MRI. Local heat release by hydrates formation leads to the dissociation of nearby hydrates. Cold seeps with high gas flow rate and pressure are more valuable for hydrate resource surveys. Abstract: Gas hydrates could occur as outcrop resources overspreading on the seafloor, coexisting with bubbling gas in activated cold seeps. This involves a complicated process of hydrate nucleation and accumulation in the sedimentary matrices as well as in the bulk water with an underlying gas plume. In addition, the escaping methane gas could also be a major concern in terms of its greenhouse effect. Consequently, the behaviors of hydrate formation in the sediments with a successive gas flow to mimic the cold seeps were monitored through magnetic resonance imaging technique in this work. It was found that the initial hydrate nucleation could occur universally throughout the sedimentary matrices resulted from an enhanced gas–water contact upon the gas flow. Specially, the substantial heat released upon hydrate formation could even locally trigger dissociation of adjacent hydrates. A faster hydrate formation was observed under higher gas flow rates and formation pressures, consolidating the dominant role of a sufficient gas–water contact in the hydrate formation. Nevertheless, large amount of residual water could still remain till the very end of the formation process; the subsequent reaction would be significantly limited by the gas diffusion barrier effect of the existing hydrate shell. The findings could provide insights into the kinetic process of hydrate formation in the cold seeps and expand our knowledge on the diverse occurrence of gas hydrate under the sea.